La situacion de los bosques tropicales - Ruíz Pérez, M.; Byron, R.N. (1999)
Tropical forest constitute the largest forest biome on Earth, hosting a large part of its biodiversity and contributing to global water and carbon cycles. The chapter analyses the pressures on these forest, their causes and differenciated results in each of the main tropical continents. Some strategies proposed to conserve tropical forest are discussed. The chapter concludes asking what would be the role of the professionals interested in management and conservation of tropical forest.